Taxonomic Demarcation of Setaria pumila (Poir.) Roem. & Schult., S. verticillata (L.) P. Beauv., and S. viridis (L.) P. Beauv. (Cenchrinae, Paniceae, Panicoideae, Poaceae) From Phytolith Signatures - Bhat, Mudassir A.; Shakoor, Sheikh A.; Badgal, Priya; Soodan, Amarjit S. (Frontiers in Plant Science, 2018)
Background and Aims: The role and significance of phytoliths in taxonomic diagnosis of grass species has been well documented with a focus on the types found in foliar epidermis and the synflorescence. The present paper is an attempt to broaden the scope of phytoliths in species diagnosis of grasses by developing phytolith signatures of some species of the foxtail genus Setaria P. Beauv. through in situ location and physico-chemical analysis of various phytolith morphotypes in different parts of the plant body. Methods: Clearing solution and dry ashing methods were employed for in situ location and isolation of phytolith morphotypes respectively. Ultrastructural details were worked out by Scanning Electron Microscopy and Transmission Electron Microscopy. Morphometric and frequency data of phytolith morphotypes were also recorded. Biochemical architecture of various phytolith types was worked out through SEM-EDX, XRD and FTIR analysis. Data were analyzed through Principal Component Analysis and Cluster Analysis. Key Results: In situ location of phytoliths revealed species specific epidermal patterns. The presence of cystoliths (calcium oxalate crystals) in the costal regions of adaxial leaf surface of S. verticillata (L.) P. Beauv. is the first report for the genus Setaria P. Beauv. Our results revealed marked variations in epidermal ornamentation and undulation patterns with a novel ‘Λ’ (Lamda) type of undulated ornamentation reported in S. verticillata (L.) P. Beauv. Dry ashing method revealed species specific clusters of phytolith morphotypes. Conclusions: The study revealed that phytoliths can play a significant role in resolution of taxonomic identity of three species of Setaria P. Beauv. Each species was marked out by a unique assemblage of phytolith morphotypes from various parts of the plant body. Apart from in situ location and epidermal patterning, diagnostic shapes, frequency distribution, size dimensions and biochemical architecture emerged as complementary traits that help in developing robust phytolith signatures for plant species.